1999
DOI: 10.1086/314703
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect and Pharmacokinetic Interaction between Nevirapine and Indinavir in Persons Infected with Human Immunodeficiency Virus Type 1

Abstract: Nevirapine and indinavir have the potential of affecting the pharmacokinetics of each other. In a prospective trial, 24 human immunodeficiency virus (HIV)-infected subjects on stable nucleoside or no therapy were treated with 800 mg of indinavir every 8 h. After 7 days, 200 mg of nevirapine a day was added for 14 days and then increased to 200 mg twice a day. At day 7 (before nevirapine), there was a sevenfold difference among the subjects in indinavir area under the curve (AUC), and there was a significant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 15 publications
(22 reference statements)
2
50
1
1
Order By: Relevance
“…Contrary to the present study, no specific approach was used to validate this cut-off. Even if the cut-off value of 1000 ng/mL, reported in our study, seems high compared with the range of 150 ng/mL to 500 ng/mL reported by others (6,7,23,33), it may be explained by the modelling estimate of C res , precisely 8 hours after last intake.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Contrary to the present study, no specific approach was used to validate this cut-off. Even if the cut-off value of 1000 ng/mL, reported in our study, seems high compared with the range of 150 ng/mL to 500 ng/mL reported by others (6,7,23,33), it may be explained by the modelling estimate of C res , precisely 8 hours after last intake.…”
Section: Discussioncontrasting
confidence: 87%
“…therapeutic drug monitoring (TDM), has shown a large interest in many diseases (3)(4)(5), to improve efficacy and minimize toxicity. Moreover, PIs are good candidates for TDM because of high inter-patient variability in plasma concentrations, binding to plasma proteins, P450 3A4 cytochrom metabolism, short half-life, drug-food and drug-drug interactions (6,7) that may lead to inadequate PIs exposure among patients receiving the same dose.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) of PIs and NNRTIs is currently valued as an additional clinical tool in HIV care, since relationships have been described between plasma concentrations and efficacy and/or toxicity. [4,[8][9][10][11] When TDM of drugs is suggested, the plasma concentration needs to be quantified with a validated method and interpretation of the result should be performed by a qualified person (e.g. clinical pharmacologist).…”
Section: Practical Issues For Use Of Interactionsmentioning
confidence: 99%
“…Awareness, recognition and management of drug interactions are important in the optimisation of pharmaceutical care to HIVinfected patients, helping to prevent adverse events and/or loss in efficacy of the drugs administered. [8][9][10][11] This review presents a tabulated overview of interactions of antiretroviral drugs and comedicated agents based on drug-drug interaction studies, case reports, population pharmacokinetic data, in vitro studies and theoretical grounds. Furthermore, a concise review is presented of the pharmacokinetics and mechanisms of interaction of antiretroviral drugs.…”
mentioning
confidence: 99%
“…5,6 In comparison, NVP, a dipyridodiazepinone and EFV, a benzoxazinone, have shown better tolerability and antiretroviral efficacy. 7,8 Skin rash is the key adverse effect observed with NVP and EFV. 9,10 Their individual propensities to cause side effects differ, with NVP showing a higher risk of cutaneous and hepatic reactions, and EFV, in addition to skin rash, having a higher risk of central nervous system effects.…”
Section: Introductionmentioning
confidence: 99%